International variation in evidence-based emergency department management of bronchiolitis: a retrospective cohort study - Franz E Babl; Marie-Pier Lirette; Ricardo M Fernandes; Javier Benito; Amy C Plint; Damian Roland; Roger Zemek; David W Johnson; Mark David Lyttle; Derek Stephens; Suzanne Schuh; Stuart Dalziel; et al. (BMJ Open)
Objectives We aimed to evaluate the international variation in the use of evidence-based management (EBM) in bronchiolitis. We hypothesised that management consistent with full-EBM practices is associated with the research network of care, adjusted for patient-level characteristics. Secondary objectives were to determine the association between full-EBM and (1) hospitalisation and (2) emergency department (ED) revisits resulting in hospitalisation within 21 days.Design A secondary analysis of a retrospective cohort study.Setting 38 paediatric EDs belonging to the Paediatric Emergency Research Network in Canada, USA, Australia/New Zealand UK/Ireland and Spain/Portugal.Patients Otherwise healthy infants 2–11 months old diagnosed with bronchiolitis between 1 January 2013 and 31 December, 2013.Outcome measures Primary outcome was management consistent with full-EBM, that is, no bronchodilators/corticosteroids/antibiotics, no chest radiography or laboratory testing. Secondary outcomes included hospitalisations during the index and subsequent ED visits.Results 1137/2356 (48.3%) infants received full-EBM (ranging from 13.2% in Spain/Portugal to 72.3% in UK/Ireland). Compared with the UK/Ireland, the adjusted ORs (aOR) of full-EBM receipt were lower in Spain/Portugal (aOR 0.08, 95% CI 0.02 to 0.29), Canada (aOR 0.13 (95% CI 0.06 to 0.31) and USA (aOR 0.16 (95% CI 0.07 to 0.35). EBM was less likely in infants with dehydration (aOR 0.49 (95% CI 0.33 to 0.71)), chest retractions (aOR 0.69 (95% CI 0.52 to 0.91)) and nasal flaring (aOR 0.69 (95% CI 0.52 to 0.92)). EBM was associated with reduced odds of hospitalisation at the index visit (aOR 0.77 (95% CI 0.60 to 0.98)) but not at revisits (aOR 1.17 (95% CI 0.74 to 1.85)).Conclusions Infants with bronchiolitis frequently do not receive full-EBM ED management, particularly those outside of the UK/Ireland. Furthermore, there is marked variation in full-EBM between paediatric emergency networks, and full-EBM delivery is associated with lower likelihood of hospitalisation. Given the global bronchiolitis burden, international ED-focused deimplementation of non-indicated interventions to enhance EBM is needed.